The prevalence of childhood sexual experiences and intimate partner violence among transgender women in China: Risk factors for lifetime suicidal ideation - Xu, Lulu; Chang, Ruijie; Chen, Yingjie; Xia, Danni; Xu, Chen; Yu, Xiaoyue; Chen, Hui; Wang, Rongxi; Liu, Yujie; Liu, Shangbin; Ge, Xin; Ma, Tiecheng; et al. (Frontiers in Public Health, 2023)
Objective: Studies highlight the impact of childhood sexual experiences (CSEs) and intimate partner violence (IPV) as risk factors on lifetime suicide ideation. Transgender women (TW) report higher rates of CSEs and IPV than cisgender people. This study aims to comprehensively assess the prevalence of CSEs and IPV and its association with lifetime suicide ideation among TW. Methods: A cross-sectional survey was conducted among 247 TW in Shenyang and Kunming, China, from April to September 2018. CSEs, IPV and lifetime suicide ideation were assessed. Logistic regression models were used to examine the association between self-reported CSEs prior to age 18, IPV in adulthood and lifetime suicide ideation. Results: Over 14.2 % of the sample (35/247) reported CSEs prior to age 18; 44.9% (111/247) reported IPV in adulthood, including 18.6% (46/247) in physical IPV, 27.1% (67/247) in trans-specific identity IPV, 31.6% (78/247) in verbal IPV, and 19.4% (48/247) in sexual IPV; 26.3% (65/247) had thought about attempting suicide for at least once. CSEs and any of IPV were significantly associated with suicide ideation for this sample population. A final stepwise multivariate logistic regression model found that physical and verbal IPV remained significantly associated with suicide ideation when controlling for other factors (ORm1 = 2.58, 95% CI = 1.163-5.724; ORm2=2.72, 95%CI = 1.334-5.547). Conclusions: Findings highlight the effects of CSEs and IPV among TW and suggest a need for suicide research in the future. Suicide prevention efforts for this invisible and vulnerable population need to be focused on those TW with physical and verbal IPV.